The Unity of Poetry and Painting and Aesthetic Spirit in the Creation of Chinese Landscape Painting - Liu, Yongliang (Journal of Fine and Applied Arts Khon Kaen University, 2025)
The integration of Chinese landscape painting with poetry has been emphasized since the beginning of landscape painting practices, as landscape painting is not only a way to convey information, but also a way to convey emotions. The fusion of these two mediums began in the Wei and Jin dynasties of China, and with the rise of literati painting in the Tang and Song dynasties, Chinese landscape painting placed more emphasis on expressing the artistic conception of landscape painting, forming a unified creative model of poetry and painting. With the development of the times, the literati improved their cultural cultivation, integrating poetry, calligraphy, painting, and printing, as well as expressing emotions in landscape works, forming a unique spirit of brushwork and artistic character. Landscape painting has also become an expression of the artist's personality and spirit.